PERBEDAAN PENAMBAHAN ONGGOK TERFERMENTASI TERHADAP PENAMPILAN PRODUKSI ITIK PEDAGING - Febri Ade Irawan; Nita opi ari kustanti; Anang Widigdyo (AVES: Jurnal Ilmu Peternakan, 2019)
This research was aimed to determine the influence of the addition of feremented cassava waste by Trichoderma viride fungus towards the appearance of duck meat production. The material used in this research was 192 types of hybrid ducks at the age of 14 days. The given treatments were: 1 feed treatment was 100. 2 feed treatment was 95%, fermented cassava waste was 5%. 3 feed treatment was 90%, fermented cassava waste was 10%. 4 feed treatment was 85%, fermented cassava waste was 15%. The observed variables were feed consumption, body weight gain, and feed conversion. The data were processed using complete random design analysis. If there was a significant difference, Duncan’s follow-up test will be conducted. The research result showed feed consumption (P<0.05), body weight gain (P>0.01), feed conversion (P>0.01). The addition of fermented cassava waste in the feed of duck affects the body weight gain and feed conversion.